Delayed rupture of a postinfarction left ventricular true aneurysm - (:unkn) unknown (ELSEVIER SCIENCE INC, 2004)
Delayed rupture of a true left ventricular aneurysm is a rare clinical condition. We report a case of a 60-year-old woman who underwent emergency surgical repair of a ruptured true aneurysm of the left ventricular inferior wall 3 months after the myocardial infarction. The repair consisted of endoaneurysmorraphy patch technique. The patient made a satisfactory recovery. (C) 2004 by The Society of Thoracic Surgeons.
Keywords: MYOCARDIAL-INFARCTION; FREE-WALL